The inhibitory action of noradrenaline and adrenaline on acetylcholine output by guinea-pig ileum longitudinal muscle strip - Paton, W. D. M. (1969)
1. Noradrenaline and adrenaline reduce the output of acetylcholine by the guinea-pig ileum longitudinal strip by up to 80%, both in resting conditions and after stimulation. The effect is graded with dose, and is detectable with noradrenaline 2 × 10(-7) g/ml. Adrenaline is approximately 4 times as active as noradrenaline, and its action after being washed out is more persistent. 2. If resting output is high, both amines have a proportionately greater effect and their action, as dosage is increased, is to reduce resting output to a basal level, relatively constant from strip to strip, of about 10 ng/g/min. 3. With stimulation, the effect of the amine is greater at low frequencies, when the output per volley is high, than at high frequencies. The effect is reduced by increasing the number of shocks delivered. There thus appears to be a basal output per volley, of the order of 1-2 ng/g/volley, which can be reached either by relatively rapid stimulation, by prolonged stimulation, or by treatment with these amines. 4. If noradrenaline is applied during continued stimulation at 40/min, the depression of acetylcholine output during its presence is followed by an augmented output when the drug is withdrawn. The magnitude of this “overshoot” increases with the duration of noradrenaline exposure. 5. Phenylephrine 4 μg/ml. and amphetamine 20 μg/ml. reduced the acetylcholine output, but isoprenaline 1 μg/ml., dopamine 1 μg/ml. and methoxamine 10 μg/ml. were ineffective. 6. Phenoxybenzamine reduced the resting output and increased the stimulation output. Of the two other blocking agents examined, phentolamine had no effect on either resting or stimulation output and ergotamine transiently reduced stimulation output. The effect of phenoxybenzamine was not due to a reaction with either adrenoceptive or muscarinic receptors. 7. Phenoxybenzamine, phentolamine and ergotamine abolished the effect of adrenaline and noradrenaline on both resting output and on output in response to stimulation. 8. In strips obtained from animals treated with reserpine and guanethidine, a rise in resting acetylcholine output and in stimulation output at low frequencies was found. In these conditions, noradrenaline was still effective. 9. Reducing the hydroxytryptamine content of the strips by treatment with p-chloro-(±)-phenylalanine did not significantly affect acetylcholine output. 10. It is concluded that acetylcholine output by the nervous networks of the longitudinal strip is under the normal control of the sympathetic by a species of presynaptic inhibition mediated by α receptors. This implies that for a tissue under dual autonomic control, withdrawal of sympathetic control will lead to a parasympathetic response which is not only unopposed but also itself enhanced.